ANALISIS PENINGKATAN KEPUTUSAN PEMBELIAN MELALUI FAKTOR – FAKTOR YANG MEMBENTUK PREFERENSI MEREK COFFEE SHOP DI SOCIAL MEDIA (Studi pada J.CO Paragon Mall, Semarang) - Sudarmono, Lea Handayani; Mudiantono, Mudiantono (Faculty of Economics and Business Diponegoro University, 2016)
Consumer lifestyle that tends to consumerist and want praticality as well as the inclusion of the value of westernized became the beginning of the rise of small- scale coffee shops as well as global level. Based business phenomenon occurs, consumers nowadays prefer to visit a coffee shop by the preference of the brand in social media. J.CO as one of the branded coffee shop seems to be less superior compared with its competitor.This study aims to determine how to improve purchasing decisions through store atmosphere, brand image, and promotion that can form preferences coffee shop brand in social media. Especially test the significance effect of brand preference on purchasing decisions.The hypothesis weretested by SEM to 200 respondents through AMOS 22.0. Result of this research found that the most influental process is the effort to improve purchasing decision by brand preference in social media which is supported through the promotion.